Original articleThe prevalence and severity of 25-(OH)-vitamin D insufficiency in HCV infected and in HBV infected patients: a prospective study - Berkan-Kawińska, Aleksandra; Koślińska-Berkan, Ewa; Piekarska, Anna (Clinical and Experimental Hepatology, 2015)
Aim of the study : To assess the prevalence and severity of vitamin D insufficiency in patients with hepatitis C virus (HCV) infection and in patients with hepatitis B virus (HBV) infection. Material and methods: This prospective study included 90 patients with chronic hepatitis C and 35 patients with chronic hepatitis B admitted to the Infectious Diseases Department between March 2013 and May 2014. Patients with chronic liver disease other than viral hepatitis, HIV co-infection, advanced liver disease and a history of diseases influencing vitamin D status were excluded. Serum vitamin D measurement as well as liver function, viral load, HCV genotype, interleukin 28 and liver fibrosis assessments were performed. Results : In all patients, the mean vitamin D serum concentration was 18.8 (± 8.9) ng/ml. The mean vitamin D level in HBV infected patients was lower than in HCV infected patients (17.6 ng/ml vs. 19.3 ng/ml; p = 0.43). Vitamin D status was assessed in relation to viral load, HCV genotype, interleukin 28 and sex, but the differences were not significant. In both groups, serum vitamin D levels were significantly lower in winter compared to summer (14.2 ng/ml vs. 23.9 ng/ml in patients infected with HCV [p < 0.000001] and 14.7 ng/ml vs. 23.8 ng/ml in patients infected with HBV [p < 0.001]). Conclusions : Our study showed that in patients with chronic hepatitis C or chronic hepatitis B, insufficient 25(OH)D concentrations occur very often, but are not associated with poor virological characteristics. The only factor influencing the vitamin D level was the season.